Three stations : an Arkady Renko novel - Smith, Martin Cruz, 1942- (New York : Simon & Schuster, 2010)
Arkady Renko returns in a new mystery about crime and corruption in the cold, dark, impenetrable landscape of modern day Moscow.
Keywords: Renko, Arkady (Fictitious character) -- Fiction; Police -- Russia (Federation) -- Moscow -- Fiction; Kidnapping -- Fiction; Moscow (Russia) -- Fiction